PENGARUH BUDAYA KESELAMATAN KESEHATAN KERJA (K3) DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT BUANA RAYA LESTARI - Dwi Astuti; Endah Asmarawati (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The purpose of this study is to examine the effect of Occupational Health and Safety Culture (K3) and Physical Work Environment on Employee Performance at PT Buana Raya Lestari. This study employs a causal associative method with a quantitative approach. The sampling technique used is saturated sampling, involving a total of 60 respondents. The results of the study indicate that Occupational Health and Safety Culture (K3) has a significant effect on Employee Performance, with a correlation coefficient of 0.512, indicating a moderate level of relationship. The hypothesis testing shows that t-count is greater than t-table (4.541 > 2.002), therefore H₀ is rejected and H₁ is accepted, which means that there is a partial effect of K3 Culture on Employee Performance at PT Buana Raya Lestari. Furthermore, the Physical Work Environment has a significant effect on Employee Performance, with a correlation coefficient of 0.658, indicating a strong level of relationship. The hypothesis testing shows that t-count is greater than t-table (6.661 > 2.002), thus H₀ is rejected and H₁ is accepted, meaning that there is a partial effect of the Physical Work Environment on Employee Performance at PT Buana Raya Lestari. Simultaneously, Occupational Health and Safety Culture (K3) and Physical Work Environment have a significant effect on Employee Performance, with a correlation coefficient of 0.562, indicating a strong relationship. The hypothesis testing shows that F-count is greater than F-table (36.629 > 3.16), therefore H₀ is rejected and H₁ is accepted, indicating that there is a simultaneous effect of K3 Culture and Physical Work Environment on Employee Performance at PT Buana Raya Lestari.